Direct observation of damage clustering in irradiated DNA with atomic force microscopy. Issue 3 (16th December 2019) - Xu, Xu; Nakano, Toshiaki; Tsuda, Masataka; Kanamoto, Ryota; Hirayama, Ryoichi; Uzawa, Akiko; Ide, Hiroshi
Abstract: Ionizing radiation produces clustered DNA damage that contains two or more lesions in 10–20 bp. It is believed that the complexity of clustered damage (i.e., the number of lesions per damage site) is related to the biological severity of ionizing radiation. However, only simple clustered damage containing two vicinal lesions has been demonstrated experimentally. Here we developed a novel method to analyze the complexity of clustered DNA damage. Plasmid DNA was irradiated with densely and sparsely ionizing Fe-ion beams and X-rays, respectively. Then, the resulting DNA lesions were labeled with biotin/streptavidin and observed with atomic force microscopy. Fe-ion beams produced complex clustered damage containing 2–4 lesions. Furthermore, they generated two or three clustered damage sites in a single plasmid molecule that resulted from the hit of a single track of Fe-ion beams. Conversely, X-rays produced relatively simple clustered damage. The present results provide the first experimental evidence for complex cluster damage.